PENGARUH PENAMBAHAN EKSTRAK ABU JERAMI DAN EKSTRAK KUNYIT TERHADAP ELASTISITAS DAN MUTU ORGANOLEPTIK MIE BASAH - Evo Tuska Serie; Hesti Nur’aini; Rahma Hidaiyanti (UNIVED Press, Universitas Dehasen Bengkulu, 2014)
Noodles is a food favored by the public. The purpose of this study was to determine the effect of rice straw ash extract and turmeric extract to the elasticity and organoleptic quality of wet noodle. This study used a completely randomized design with the addition of straw ash extract concentration treatment variations ( 3%, 5%, and 7% ) , and the addition of turmeric extract ( 1%, and 1.5% ). The results of the analysis indicate that the elasticity of wet noodles all treatments gave a real difference at a significance level of 5%. The organoleptic analysis showed that all treatments gave significant effect on color, flavor, aroma, firmness at a significance level of 5 % , which is highest rank in the treatment of straw ash extract concentration of 5% and 1 % turmeric extract.Keywords: wet noodles, straw ash extract, turmeric extract